Speculum versus digital insertion of Foley catheter for induction of labor in Nulliparas with unripe cervix: a randomized controlled trial - Hang Min Chia; Peng Chiong Tan; Sze Ping Tan; Mukhri Hamdan; Siti Zawiah Omar (BMC, 2020)
Abstract Background Induction of labor (IoL) is an increasingly common obstetric procedure. Foley catheter IoL is recommended by WHO. It is associated with the lowest rate of uterine hyperstimulation syndrome and similar duration to delivery and vaginal delivery rate compared to other methods. Insertion is typically via speculum but digital insertion has been reported to be faster, better tolerated and with similar universal insertion success compared to speculum insertion in a mixed population of nulliparas and multiparas. Transcervical procedure is more challenging in nulliparas and when the cervix is unripe. We evaluated the ease and tolerability of digital compared to speculum insertion of Foley catheter for induction of labor in nulliparas with unripe cervixes. Methods A randomized trial was performed in a university hospital in Malaysia. Participants were nulliparas at term with unripe cervixes (Bishop Score ≤ 5) admitted for IoL who were randomized to digital or speculum-aided transcervical Foley catheter insertion in lithotomy position. Primary outcomes were insertion duration, pain score [11-point Visual Numerical Rating Scale (VNRS)], and failure. All primary outcomes were recorded after the first insertion. Results Data from 86 participants were analysed. Insertion duration (with standard deviation) was 2.72 ± 1.85 vs. 2.25 ± 0.55 min p = 0.12, pain score (VNRS) median [interquartile range] 3.5 [2-5] vs. 3 [2-5] p = 0.72 and failure 2/42 (5%) vs. 0/44 (0%) p = 0.24 for digital vs speculum respectively. There was no significant difference found between the two groups for all three primary outcomes. Induction to delivery 30.7 ± 9.4 vs 29.6 ± 11.5 h p = 0.64, Cesarean section 25/60 (64%) vs 28/64 (60%) RR 0.9 95% CI p = 0.7 and maternal satisfaction VNRS score with the birth process 7 [IQR 6-8] vs 7 [7-8] p = 0.97 for digital vs. speculum arms respectively. Other labor, delivery and neonatal secondary outcomes were not significantly different. Conclusion Digital and speculum insertion in nulliparas with unripe cervixes had similar insertion performance. As digital insertion required less equipment and consumables, it could be the preferred insertion method for the equally adept and the insertion technique to train towards. Trial registration This trial was registered with ISRCTN registration number 13804902 on 15 November 2017.